Boosting Fine Motor Abilities in Children with Cerebral Palsy Through LEGO Constructive Play in Special Schools - Wiwik Dwi Hastuti; Mohd Hanafi Mohd Yasin; Rizqi Fajar Pradipta; Muhammad Nurrohman Jauhari (AL-ISHLAH: Jurnal Pendidikan, 2025)
Children with cerebral palsy (CP) typically exhibit lower fine motor skills compared to their typically developing peers. Various interventions, including constructive LEGO play, have been explored to support fine motor skill development. This study examines the effectiveness of constructive LEGO play in enhancing fine motor skills in children with CP at SDLB Putra Jaya Malang. A Single-Subject Design (SSD) with an A-B-A format was employed. Data were collected through structured observations and assessments of fine motor skills during baseline, intervention, and post-intervention phases. Findings indicate a notable improvement in fine motor skills from the first baseline (A1) to the intervention phase (B), with sustained progress in the second baseline (A2) after the intervention was withdrawn. This suggests that constructive LEGO play positively influences fine motor skill development in children with CP. The study highlights the potential of LEGO-based activities as an engaging and effective tool for improving fine motor coordination in children with CP. The observed progress reinforces the need for structured and repetitive fine motor activities in special education settings. Constructive LEGO play proves to be a beneficial intervention for enhancing fine motor skills in children with CP. Its integration into therapy and special education programs could provide long-term benefits. Further research is recommended to explore its scalability and long-term impact.